Ultrasound-Assisted Emulsification Microextraction for Determination of 2,4,6-Trichloroanisole in Wine Samples by Gas Chromatography Tandem Mass Spectrometry - Fontana, Ariel Ramón (2010)
A fast and effective microextraction technique is proposed for preconcentration of 2,4,6-trichloroanisole (2,4,6-TCA) from wine samples prior gas chromatography tandem mass spectrometric (GC-MS/MS) analysis. The proposed technique is based on ultrasonication (US) for favoring the emulsification phenomenon during extraction stage. Several variables influencing the relative response of the target analyte were studied and optimized. Under optimal experimental conditions, 2,4,6-TCA was quantitatively extracted achieving enhancement factors (EF) ≥ 400, limits of detection (LODs) 0.6-0.7 ng L-1 with RSDs ≤11.3%; when 10 ng L-1 2,4,6-TCA standard- wine sample blend was analyzed. The calibration graphs for white and red wine were linear within the range of 5-1000 ng L-1 and estimation coefficients (r2) were ≥0.9995. Validation of the methodology was carried out by standard addition method at two concentrations (10 and 50 ng L-1) achieving recoveries >80% indicating satisfactory robustness of the method. The methodology was successfully applied for determination of 2,4,6-TCA in different wine samples.